AKTIVITAS INHIBISI ASETILKOLINESTERASE EMPAT JENIS SAYURAN SECARA IN VITRO - Maulita Cut Nuria; Elin Yulinah Sukandar; Asep Gana Suganda; Muhamad Insanu (Universitas Wahid Hasyim Semarang, 2019)
ABSTRACTAcetylcholine is a conducting compound of nerve excitatory (neurotransmitter), while acetylcholinesterase is an enzyme that can hydrolyze the acetylcholine into choline and acetic acid. This reaction is needed so that the nerves can return to take a rest after the activation process, but it can cause damage to the cells in the brain. The most common case is dementia characterized by memory loss. The prevalence of this disease is lower in China and some other Asian countries compared to the United States. It supposed because food consumption commonly by Asians contain vegetables. Extracts derived from vegetables potentially inhibit the activity of acetylcholinesterase (AChE) enzyme which related to chemical contents of the plant. This research aims to investigate the inhibitory activity of acetylcholinesterase enzyme from 4 types of vegetables namely soybean sprouts (bean sprout of Glycine max (L.) Merr.), green bean sprouts (bean sprout of Vigna radiata), carrot (Daucus carota L.), and winged beans (Psophocarpus tetragonolobus (L.) DC.) by in vitro with the Ellman method. Total phenolic and flavonoids contents from fourth types of extracts were also determined. The winged beans extract had the smallest total phenolic and flavonoid contents, but the inhibitory activity against AChE was the biggest. The results showed that IC50 extract of winged beans was 893.86 μg/ml, IC50 carrot extract higher than 1500 μg/ml while the other extracts had no activity. The winged beans extract potential to be further developed as an inhibitor AChE.Keywords : inhibitor of acetylcholinesterase, IC50, vegetables